Rynek jako czynnik ograniczający wolność słowa - Gołata, Krzysztof (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2007)
The author attempts to consider the relationship between freedom of speech and the principles of the free market in three aspects. Firstly, economic recession reduces the market offer and restricts access to newspapers and magazines. Secondly, the concentration of capital in the media and dropping of prices results in a limited number of titles circulating, thus restricting the amount of opinions and news releases reaching the readers. Thirdly, the dependence of editors on the advertisers makes „the one who pays dictate the terms, i.e. select the information and opinion and present himself in good light”. The opinion is frequently encountered that „freedom of speech is the freedom of the editor as opposed to that of a journalist”, which is mainly voiced by the former.